Mental health of residents of radioactively contaminated territories of the Chelyabinsk region in the late period after the resettlement - E. Yu. Burtovaia (Радиационная гигиена)
In case of radiation accidents, one of the radical protective measures is the evacuation of residents from contaminated areas. Its purpose is to reduce the possible radiation effect to the population. At the same time, evacuation itself becomes a serious stressful factor that has a negative impact on a person’s health and mental status. The objective of this work is to assess the state of mental health of residents of the Muslyumovo settlement in the Chelyabinsk region (the territory exposed to radioactive contamination as a result of radioactive waste releases into the Techa River) who participated in the resettlement program in the period from 2006 to 2010. Mental health was assessed twice: primarily in 2008-2010 against the background of resettlement, and again in 2019-2020, 10 or more years after the resettlement. The study includes 2 groups formed by random selection. The main group consisted of 100 persons from among the participants of the resettlement program. The comparison group included 80 persons living in the territories exposed to radioactive contamination, but not participating in the resettlement program. According to the main socio-hygienic characteristics, the groups are homogeneous and comparable. The following methods were used: clinical, clinical and psychological, and the method of statistical processing of materials. As a result, it was found that both in the primary and in the repeated study, residents of the Muslyumovo settlement, Chelyabinsk region, participating in the resettlement program, were statistically significantly more likely (p<0.001) to have mental disorders and behavioral disorders (neurotic, stress-related and somatoform disorders (F 40)), compared with the control group. Also, according to the results of the survey, statistically significantly more often the psychogenic effect of resettlement (p≤0.001) was detected in patients of the main group. The data obtained suggest a long-term effect of resettlement on the mental health of the population involved. Understanding the consequences of the protective measures carried out (resettlement) will clarify the criteria for their application, as well as predict the manifestations of mental maladaptation in the population with the potential development of radiation accidents.